(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
This article analyzes demography, social demography, and development trends. The theory of demographic transition and J. Caldwell’s concept are deeply analyzed. Reproductive behavior and family relationships are considered central to demography. Among the methodological approaches are statistical, sociological, and historical methods. The article focuses on contemporary demographic problems and the need to manage them.